Entamoeba histolytica Cyclooxygenase-Like Protein Regulates Cysteine Protease Expression and Virulence - Shahi, Preeti; Moreau, France; Chadee, Kris (Frontiers in Cellular and Infection Microbiology, 2019)
The intestinal protozoan parasite Entamoeba histolytica (Eh) causes amebiasis associated with severe diarrhea and/or liver abscess. Eh pathogenesis is multifactorial requiring both parasite virulent molecules and host-induced innate immune responses. Eh-induced host pro-inflammatory responses plays a critical role in disease pathogenesis by causing damage to tissues allowing parasites access to systemic sites. Eh cyclooxygenase (EhCox) derived prostaglandin E2 stimulates the chemokine IL-8 from mucosal epithelial cells that recruits neutrophils to the site of infection to exacerbate disease. At present, it is not known how EhCox is regulated or whether it affects the expression of other proteins in Eh. In this study, we found that gene silencing of EhCox (EhCoxgs) markedly increased endogenous cysteine protease (CP) protein expression and virulence without altering CP gene transcripts. Live virulent Eh pretreated with arachidonic acid substrate to enhance PGE2 production or aspirin to inhibit EhCox enzyme activity or addition of exogenous PGE2 to Eh had no effect on EhCP activity. Increased CP enzyme activity in EhCoxgs was stable and significantly enhanced erythrophagocytosis, cytopathic effects on colonic epithelial cells and elicited pro-inflammatory cytokines in mice colonic loops. Acute infection with EhCoxgs in colonic loops increased inflammation associated with high levels of myeloperoxidase activity. This study has identified EhCox protein as one of the important endogenous regulators of cysteine protease activity. Alterations of CP activity in response to Cox gene silencing may be a negative feedback mechanism in Eh to limit proteolytic activity during colonization that can inadvertently trigger inflammation in the gut.